The physician actor and actor physician. - De Caprio, Lorenzo; Cinque, Paola (Medicina e Morale, 2001)
This paper explains affinities and the relationship between theatre and medicine in western culture. From one hand, the authors delineate the theatrical characteristics of the medical practice; on the other hand, they stress the role of social criticism played by the figure of the doctor in the history of theatre, by addressing health professionals to the respect of ethical and human values which are typical of medical practice. The actor is drawing profile of the doctors' role in the western culture and their relationship with human suffering and death. At the same time, a historical run is made from the Greek tragical poetry, through Christian humanism, leading to the contemporary refusal of humanism.